Miniscope GRIN Lens System for Calcium Imaging of Neuronal Activity from Deep Brain Structures in Behaving Animals. Issue 1 (13th October 2018) - Zhang, Lifeng; Liang, Bo; Barbera, Giovanni; Hawes, Sarah; Zhang, Yan; Stump, Kyle; Baum, Ira; Yang, Yupeng; Li, Yun; Lin, Da‐Ting
Abstract: Visualizing neural activity from deep brain regions in freely behaving animals through miniature fluorescent microscope (miniscope) systems is becoming more important for understanding neural encoding mechanisms underlying cognitive functions. Here we present our custom‐designed miniscope GRadient INdex (GRIN) lens system that enables simultaneously recording from hundreds of neurons for months. This article includes miniscope design, the surgical procedure for GRIN lens implantation, miniscope mounting on the head of a mouse, and data acquisition and analysis. First, a target brain region is labeled with virus expressing GCaMP6; second, a GRIN lens is implanted above the target brain region; third, following mouse surgical recovery, a miniscope is mounted on the head of the mouse above the GRIN lens; and finally, neural activity is recorded from the freely behaving mouse. This system can be applied to recording the same population of neurons longitudinally, enabling the elucidation of neural mechanisms underlying behavioral control. © 2018 by John Wiley & Sons, Inc.